Metabolomic dynamics reveals oxidative stress in spongy tissue disorder during ripening of mangifera indica l. fruit - Oak, Pranjali; Deshpande, Ashish; Giri, Ashok; Gupta, Vidya (Metabolites, 2019)
Spongy tissue disorder, a mesocarp specific malady, severely affects the flavor and pulp characters of Alphonso mango fruit reducing its consumer acceptability. Here, we investigated comparative metabolomic changes that occur during ripening in healthy and spongy tissue-affected fruits using high resolution mass spectrometric analysis. During the spongy tissue formation, 46 metabolites were identified to be differentially accumulated. These putative metabolites belong to various primary and secondary metabolic pathways potentially involved in maintaining the quality of the fruit. Analysis revealed metabolic variations in tricarboxylic acid cycle and gamma amino butyric acid shunt generating reactive oxygen species, which causes stressed conditions inside the mesocarp. Further, reduced levels of antioxidants and enzymes dissipating reactive oxygen species in mesocarp deteriorate the fruit physiology. This oxidative stress all along affects the level of amino acids, sugars and enzymes responsible for flavor generation in the fruit. Our results provide metabolic insights into spongy tissue development in ripening Alphonso mango fruit.
Keywords: gamma amino butyric acid shunt; mango metabolomics; Oxidative stress; spongy tissue disorder; tricarboxylic acid cycle

Transcriptional and translational perturbation in abiotic stress induced physiological activities and metabolic pathway networks in spongy tissue disorder of mango fruit - Oak, Pranjali; Jha, Vineet; Deshpande, Ashish; Tanpure, Rahul; Dawkar, Vishal; Mundhe, Swapnil; Ghuge, Sandeep; Prabhudesai, Shrikant; Krishanpal, Anamika; Jere, Abhay; Giri, Ashok; Gupta, Vidya (Postharvest Biology and Technology, 2022)
Spongy tissue formation is economically the most detrimental but agriculturally less focused physiological disorder in mango. `Alphonso' cultivar is highly prone to oxidative stress induced spongy tissue disorder impacting biochemical and metabolic profile, thereby affecting pulp quality and nutritional value of the fruit. In the present study, comparative analysis of spongy and healthy mesocarp tissues of `Alphonso' mango by transcriptomics using Illumina sequencing and proteomics using LC-MS approaches, respectively identified and quantified many genes and proteins in the metabolic pathways responsible for the spongy tissue development. The table green and the mid ripe stages of `Alphonso' fruit ripening were evaluated by the transcriptomic study and outcomes were validated using proteomic investigations for all the four ripening stages. Colossal amount of data including 30,582 transcripts, 10,800 gene ontologies and 387 putative proteins was generated from this analysis. Current multi-omics exploration revealed the development of abiotic stress (mainly oxidative stress) induced perturbations in various metabolic pathways and their interconnections, leading to the spongy tissue formation in mango. This further unfolded the altered cell wall degradation, ethylene and flavonoid biosynthesis, fruit ripening and flavor formation, thus hampering the fruit specific characteristics in mango with spongy tissue disorder.
Keywords: Oxidative stress; Proteome; spongy tissue disorder; Transcriptome; ` Alphonso ` mango